Trajnostna arhitektura v kontekstu vzgoje in izobraževanja: nekateri odgovori osnovnošolskih učiteljev na aktualno temo - Cencič, Majda; Mlinar, Anton (Revija za elementarno izobraževanje, 2011)
Sustainable Architecture in the Context of Education: Reponses of Primary School Teachers on the Topical Subject. The concept of sustainability and a sustainable and ecological development are common debate topics in today’s society. This paper discusses the concept of sustainability in green building with regard to schools. The research was conducted on a representative sample of primary school teachers, focusing on some of their opinions on green building. We asked them which aspect of building they favoured and how often they asked themselves certain questions about the school they taught in. Furthermore, we were interested to see whether we would find age-related differences. To this end, teachers were divided into two groups, namely, teachers of up to 35 years of age and teachers over 35. We were surprised to find that teachers over 35 had a more positive attitude towards green building in schools compared to their younger colleagues. Based on the results, we came to a conclusion that the topics pertaining to ecology and sustainable development are neglected in today’s education. However, making them part of school curriculum is not enough, as the opinions and attitudes of teachers on sustainable and ecological issues also have an important impact on the subject-matter itself.